AKIBAT HUKUM YANG DI TIMBULKAN DARI SUATU PERKAWINAN BEDA AGAMA DI INDONESIA (Analisis Penetapan No. 91/Pdt.P/2022/PN Bks) - Murnita, Eva; Siregar, Abdul Rahman Maulana; Aspan, Henry (Universitas Negeri Medan, 2025)
The reality in the life of society, interfaith marriages occur as an undeniable reality. In practice, many couples want to live together but do not get married because they are based on different religions or beliefs. There are also couples who have lived together or